DESAIN PENELITIAN GROUNDED THEORY: LOGIKA METODOLOGIS DAN KONSTRUKSI TEORI KONTEKSTUAL DALAM PENDIDIKAN - Muhammad Abdillah; Salamah; Dina Hermina (Jurnal Riset Multidisiplin Edukasi, 2026)
Traditional positivist frameworks in educational and social research often over-rely on pre-existing grand theories, resulting in the reduction and "dehumanization" of unique social contexts. Grounded Theory emerges as a rigorous inductive-abductive methodology to construct systematic theories directly rooted in empirical field data. This study aims to analyze the fundamental concepts, philosophical origins (symbolic interactionism), and methodological procedures of Grounded Theory, and to formulate its operational steps within educational research contexts. Operating as a qualitative-descriptive inquiry, this library research critically analyzes primary literature from Glaser, Strauss, Corbin, and Charmaz, utilizing content analysis and comparative triangulation to map out its systematic coding processes. The findings demonstrate that Grounded Theory is a comprehensive research design—rather than a mere data analysis technique—guided by key principles: theoretical sensitivity, theoretical sampling, the constant comparative method, structured coding (open, axial, and selective), memo writing, and theoretical saturation. A rigorous operational simulation of coding regarding facility provisioning for educational needs assessments is provided to illustrate its practical mechanics. The study concludes that Grounded Theory effectively bridges the gap between abstract grand theories and empirical reality, offering a robust, scientifically rigorous, and contextually responsive pathway to develop localized educational theories that are highly relevant to contemporary Indonesian and Islamic education management.